Correlação clínico patológica entre as imunomarcações de E-caderina e receptores de estrógeno nos tumores de mama em cadelas - Ens, Maria Thereza Bonfim (2020)
The relationship between the oestrogen receptor (ER) and epithelial (E-) cadherin expression, as detected by clinicopathological features and immunohistochemical methods, was evaluated in 111 canine mammary tumours. The majority (n = 95; 85.58%) of tumours were histologically malignant and subclassified as grade I (n = 42), grade II (n=31), or grade III (n=2022). There was a significant statistical association between grade III malignancy and negativeimmunostaining for oestrogen (p= 0.01). No significant associations could be established between histological classification (neoplasm, benign or malignant) and immunostaining for 23 ER and E-cadherin. Twenty-one (22.10%) of 95 malignant mammary tumours had metastasized. Twenty-four simple mammary carcinoma (n = 9) was significantly associated with negative ER expression (p = 0.03), suggesting a poor prognosis. These findings emphasize the necessity of improving prognostic factors in canine mammary tumours.